30-day survival and injury severity in traffic accidents in Iran: A mixed-method study protocol - Amin Talebi; Hamidreza Khankeh; Mohammad Saatchi; Mehrdad Farrokhi; Timoor Hosseini (PLoS ONE, 2025)
Background Today, one of the greatest global challenges, particularly in developing countries, is traffic accidents and their associated consequences. The severity of injuries from these accidents often leads to serious outcomes for victims, including long-term disabilities and high mortality rates. Deaths from traffic accidents may occur at the scene, during transportation, or in hospitals. In light of the existing challenges in coordination between law enforcement and healthcare systems regarding traffic accident fatalities in our country, this study aims to: 1. Determining the 30-day survival rate and its relationship with injury severity among traffic accident victims in Khorramabad in 2025. 2. Identifying key challenges and proposing effective solutions for improving traffic accident management in Khorramabad. Methodology This mixed-methods study will be conducted in three phases: 1. Phase 1 (Quantitative): A prospective cohort study will investigate the relationship between injury severity (as measured by scales such as ISS)and 30-day survival rates. 2. Phase 2 (Qualitative): Purposive sampling will be used to conduct semi-structured interviews with stakeholders (victims, families, EMTs, healthcare providers, etc.). Qualitative data will be analyzed via inductive content analysis (Hsieh & Shannon approach) to identify challenges and solutions in traffic accident management. 3. Phase 3 (Integration): Findings from Phases 1 and 2 will be finalized and presented to policymakers, managers, and experts. The Delphi method will be used to prioritize challenges/solutions and finalize evidence-based recommendations.Results will be disseminated through: Peer-reviewed publications in reputable journals. Policy briefs tailored for officials to improve traffic accident management.